1978
DOI: 10.1111/j.1151-2916.1978.tb09310.x
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of Lead Glasses in Acid Media: I, Leaching Kinetics

Abstract: The leaching kinetics of lead glasses (25 to 35 mol% PbO-75 to 65 mol% SO,; some with K 2 0 and additions) were determined in 10% acetic acid. Except for a ternary glass (Si0,-PbO-KZO) which had a linear dependence on time, all compositions exhibited a linear dependence on the square root of time for the amount of Pb and K removed. Increasing the SO,: PbO ratio or the AI,O,i content improved the durability whereas adding K,O to a binary PbO-Si02 glass greatly increased the corrosion rate. Activation energies f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…In addition to alkali ions, the Pb 2þ cations, acting as network modifiers, are significantly diffused and replaced by H þ ions from the corrosion medium [9 -11]. Accelerated ageing experiments aimed to the study of specific process of corrosion of lead and lead-alkali glasses performed by Wood and Blanchere [12,13] indicated that the removal of Pb 2þ and K þ from leadpotassium glasses approaches two different dependences on time: at short times, a proportionality of the released amount of ions with the square root of time was obtained, diffusion acting as a rate-determining factor; at long times, the amount of released ions was found to be proportional to time, suggesting that the silica dissolution is the rate-limiting factor instead of proton or ion diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to alkali ions, the Pb 2þ cations, acting as network modifiers, are significantly diffused and replaced by H þ ions from the corrosion medium [9 -11]. Accelerated ageing experiments aimed to the study of specific process of corrosion of lead and lead-alkali glasses performed by Wood and Blanchere [12,13] indicated that the removal of Pb 2þ and K þ from leadpotassium glasses approaches two different dependences on time: at short times, a proportionality of the released amount of ions with the square root of time was obtained, diffusion acting as a rate-determining factor; at long times, the amount of released ions was found to be proportional to time, suggesting that the silica dissolution is the rate-limiting factor instead of proton or ion diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…As for alkali silicate glasses, a square root of time rate law was followed by a linear rate law for optical lead silicate glasses (SiO 2 65 mol %, PbO 25-35 mol %, K 2 O 0-10 mol %, Al 2 O 3 0-2 mol %) under acetic acid static corrosion conditions [217]. Activation energies were $50 kJ/mol.…”
Section: I8 Optical Glassesmentioning
confidence: 99%
“…Activation energies were $50 kJ/mol. As for alkali ions in alkali silicate glasses, diffusion-controlled surface depletion profiles were observed for Pb release from the glass [218].…”
Section: I8 Optical Glassesmentioning
confidence: 99%
“…Lead silicate glasses are also of considerable interest for their peculiar thermal, optical, and mechanical properties, and their structural chemistry has drawn attention, in particularly as regards Pb 2+ leaching . In fact, different proposals have been put forward about the structural role played by lead centers as some act as network modifiers with a sixfold coordinated environment, while others act as network formers and have a lower coordination number .…”
Section: Introductionmentioning
confidence: 99%